Asymmetric Three‐Component Heck Arylation/Amination of Nonconjugated Cyclodienes - Zhu, Daoyong; Jiao, Zhiwei; Chi, Yonggui Robin; Gonçalves, Théo P.; Huang, Kuo‐Wei; Zhou, Jianrong Steve (Angewandte Chemie International Edition, 2020)
Substituted cyclohexylamines are becoming increasingly important in drug discovery. Asymmetric Heck insertion/amination of nonconjugated cyclodienes proceeds to give 5‐aryl cyclohexenylamines with good enantioselectivity and exclusive trans configurations. Primary and secondary anilines, indoline, and benzylamines are suitable amines. The weakly donating diphosphite Kelliphite forms a deep unsymmetrical pocket, which is essential for stereoselective anti attack of amines. Deep pockets: Heck arylation of nonconjugated dienes under palladium catalysis produces π‐allyl complexes, which can be trapped by various amines to give substituted cyclohexenylamines with good enantioselectivity and exclusively trans configuration. The weakly donating diphosphate ligand Kelliphite forms a deep unsymmetrical pocket, which is essential for stereoselective anti attack of amines.